Recent advances and future developments in Fe-based amorphous soft magnetic composites - Lu, Shuhan; Wang, Minggang; Zhao, Zhankui (Journal of non-crystalline solids, 2023)
•Overview of the present development of Fe-based amorphous soft magnetic composites.•Development of coating in the direction of insulation and magnetic permeability.•Main issues to be solved in the molding of amorphous soft magnetic composites.•Need for high-frequency miniaturization of electrical and electronic devices. Soft magnetic composites (SMCs) are a crucial material in the process of electromagnetic conversion, playing a critical role in power production, transmission and utilization. Third-generation semiconductors necessitate soft magnetic materials with distinctive characteristics, such as high response, high power density and low total loss. Fe-based amorphous soft magnetic alloys exhibit exceptional soft magnetic properties, including high saturation magnetization, low coercivity and high permeability. To mitigate high eddy current loss, the utilization of ultra-thin laminating or powder composite cores is recommended. Amorphous soft magnetic composites (ASMCs) are produced through powder metallurgy techniques utilizing insulated and/or coated amorphous soft magnetic powders. The paper presents an overview of Fe-based ASMCs development history, various types of insulating, coating preparation methods, molding preparation technology, heat treatment process and recent significant achievements. Additionally, the study highlights future research hotspots and trends in the discipline of Fe-based ASMCs, along with critical concerns, development prospects and directions faced.